Saúde, desenvolvimento e políticas públicas: o modelo de gestão da EBSERH no Hospital Universitário Alcides Carneiro - Araújo, Maria do Socorro Campos (2021)
This paper aims to analyze the change in the management of the Alcides Carneiro University Hospital, linked to the Federal University of Campina Grande, from the formalization of contract No. 46/2015, on December 9, 2015, with the Brazilian Hospital Services Company (EBSERH), created through Law nº 12.550, of December 15, 2011, with the purpose of administering the network of university hospitals linked to the Federal Universities of Brazil. Data from HUAC were analyzed, related to the production of services, hiring of personnel and budgetary contribution, from the period 2013 to 2020. The research is a case study with an inductive approach method. As for the purpose, the research is applied, being exploratory and descriptive in terms of objectives. It has a quantitative nature, being classified as documentary, secondary data. Data were collected through official websites of the EBSERH, HUAC, the Ministries of Health and the Ministry of Education, as well as a bibliographic consultation on the subject, available in the Scielo and Google Academic systems. From the analysis of the data, the extinction of precarious employment contracts can be observed, which were replaced by the hiring of workers through public competition, an increase in the offer of services, especially outpatient services, an increase in the acquisition of medical and electro-electronic equipment, as well as furniture and structural reforms, carried out with resources from the National Program for the Restructuring of Federal University Hospitals (REHUF), created by Decree No. 7.082, of January 27, 2010. Data analysis of the three aspects proposed in the study points out that the new model of management at HUAC, presents changes that demonstrate that they point to proximity to the principles of the SUS and to the proposal for development along the lines of Amartya Sen's theory, contributing to the development of the region in which it operates if the search for achievement of the highest precepts advocated in health policies in Brazil.